Dehydrated strawberries for probiotic delivery: Influence of dehydration and probiotic incorporation methods - Oliveira, Aline Soares [UNESP]; Niro, Carolina Madazio; Bresolin, Joana Dias; Soares, Viviane Faria; Ferreira, Marcos David; Sivieri, Katia [UNESP]; Azeredo, Henriette M.C. (Elsevier, 2021)
In this study, dehydrated strawberries have been proposed as probiotic carriers. Strawberries were cut into halves, incorporated with probiotic Bacillus coagulans BC4 by two alternative methods (impregnation and alginate coating) and submitted to two alternative drying methods (freeze drying - FD - and oven drying - OD). Six treatments were carried out, namely: FD and OD (no probiotic), I-FD, I-OD, C-FD, and C-OD (I- and C- meaning impregnation and coating respectively). While the probiotic incorporation method affected a few properties of the resulting products (mainly the probiotic viability on processing), the drying methods resulted in remarkable differences. The freeze-dried strawberry halves presented higher retention of chemical (ascorbic acid and anthocyanin contents) and physical properties (shape, color, and firmness) as well as a better acceptance and higher probiotic viability, resulting in higher probiotic release into the small intestine. The I-FD treatment resulted in the highest probiotic viability after processing and through a 6-month storage (near 8 log cfu.g−1).
Keywords: Edible coatings; Food dehydration; Fragaria × ananassa; Non-dairy probiotic foods